Clinico - Pathological Correlation of Thyroid Swellings - Jain, Sharad; Nayak, Rashmi; Totade, Sanjay; Shukla , Neelam (International Journal of Medical Research and Review, 2014)
Introduction: Thyroid being an actively functioning gland is subjected to series of disturbances, both physiological and pathological. It may be affected by various disorders like developmental, inflammation, hyperplastic and neoplastic that may present with similar sign and symptoms. Almost any disorder of thyroid can present as a nodule. The thyroid nodule is common problem faced by the clinicians as they cause apprehension due to their unpredictable behaviour. Method: A total of 110 patients were studied. All patients underwent FNAC after prior consent. FNAC was done with aseptic precautions by using 23 gauze needles, non-aspiration technique. Material obtained was smeared on 2 glass slides, air dried and stained with Leishmann’s stain. Remaining wet slides fixed by using ethanol and were stained with hematoxylin and eosin (H&E) method. Pre-operative FNAC results were then compared with the definitive histological diagnosis. Result: Incidence of malignancy in thyroid nodules was 8.18%. Sensitivity and specificity in the present study was 85.7% and 96.4%, respectively with PPV, NPV and diagnostic accuracy of 92.3%, 93.1% and 92.9%, respectively. False positive and false negative error rate was 2.4 and 4.8 respectively. Conclusion: Definitive diagnosis of either benign or malignant can be suggested by FNAC and accordingly line of management can be planned. So we can avoid unnecessary surgeries for benign lesions and reduce the cost of hospitalisation.